Differences in immune cells and gene expression in human milk by parity on integrated scRNA sequencing - Dae Yong Yi; Hong-Jai Park; Min Sun Shin; Hyoungsu Kim; Sang Jin Lee; Insoo Kang (Clinical and Experimental Pediatrics)
Background Human breast milk (HBM) is an important source of tolerogenic immune mediators that influence the infant immune system. HBM-derived immune components are affected by various factors; however, few studies have examined the relationship between parity and immune cell profiles of HBM. Purpose This study aimed to clarify the effects of parity on HBM immune cell heterogeneity and gene expression by integrating and analyzing publicly available single-cell RNAsequencing (scRNA-seq) datasets. Methods We clarified the effects of parity on HBM immune cell heterogeneity and gene expression by integrating and analyzing publicly available scRNA-seq datasets. Results The proportion of innate immune cells was significantly higher in the primiparous versus multiparous group, whereas the proportion of adaptive immune cells was significantly higher in the multiparous group (P=0.021). The 2 immune clusters were reannotated and classified into monocyte, T/B cell, and CD45¯ groups. The proportions of monocytes and T/B cells were higher in the primiparous and multiparous groups, respectively. In a gene set enrichment analysis of monocytes, genes with a direct role in the infant immune system and immune response-related genes were more highly expressed in the primiparous group. Conclusion Our results support the parity-dependent differences in gene expression between innate and adaptive immune cells.